Exploring the factors and mechanisms involved in triggering the alternative lengthening of telomeres pathway - Kent, T (2021)
Maintaining replicative immortality is a crucial step in the development of cancers and is achieved by activating a telomere lengthening mechanism. While the majority of cancers rely on upregulation of telomerase, approximately 10-15% of cancers achieve telomere length maintenance through a telomerase-independent mechanism referred to as the Alternative Lengthening of Telomeres (ALT) pathway. ALT cancers exhibit a number of characteristic markers and recent work has sought to understand the mechanisms that underly the generation of these markers and of ALT telomere maintenance.